2008
DOI: 10.1007/s00268-008-9491-2
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Postoperative Ileus—Definition, Risk Factors, and Predictors after Surgery

Abstract: We have identified two risk factors (EBL and TOD) that are independently associated with duration of POI. Our data suggest that with the definition of abnormal prolonged postoperative ileus as the number of days above the 3rd quartile, an ileus greater than 6 days serves as a better clinical definition of prolonged POI than 3 days, the measure that has previously been suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
188
3
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(202 citation statements)
references
References 26 publications
6
188
3
5
Order By: Relevance
“…Although these pharmacological agents reduce ileostomy output, they are not commonly used in perioperative HOI treatment, as the perioperative use of opioids has been shown to increase the risk of ileus (11). It has been reported that Clostridium difficile (C. difficile) infection often occurs in HOI (12); however, C. difficile was not detected in our cases (data not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Although these pharmacological agents reduce ileostomy output, they are not commonly used in perioperative HOI treatment, as the perioperative use of opioids has been shown to increase the risk of ileus (11). It has been reported that Clostridium difficile (C. difficile) infection often occurs in HOI (12); however, C. difficile was not detected in our cases (data not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Other accelerated recovery pathways have shown benefits of pain control with multimodal 28 and regional 29 -32 analgesia. As opioid requirements have been identified as one of two independent risk factors for prolonged postoperative ileus, any pathway that minimizes use of opioids should decrease the risk of ileus 33 . The other risk, estimated blood loss, may be less modifiable 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the applicability of a retrospective analysis might greatly vary in different centers, depending on patients' characteristics. For instance, none of the three independent risk factors in this scoring system reached significance in the analyses from other databases [38,39,40]. Different centers, therefore, need to consider or even reevaluate the applicability of the predictive scoring systems from other databases.…”
Section: Discussionmentioning
confidence: 99%